International Technology Transfer and Economic Development - Pavan, Badrinarayanan; Shafighi, Najla (Archives of Business Research, 2022)
This paper intends to critically examine the concept of International Technology Transfer, considering Japan whilst they provide necessary tech advancements ideas for innovation to another transferee country i.e., India. This country realized the high significance of the technology transformation for its fast economic and commercial growth. We will also be analyzing Japan’s position as a tech superpower and an economic superpower. To analyze the economic development, a comparative study will be made with India. Here, Japan is the transferor, and India is selected due to its high intentions for development, and hence it needs support from developed nations with better technology. In this study, we take the balance of payment as the dependent variable and GDP, inflation rate, Exchange rate, and FDI as independent variables. Data is analyzed and results are obtained using regression which helps us analyze quantitatively. The data from the World Bank database about India and Japan has been obtained for the periods 2000-2019. This study helps us to interpret and find the key impacting factors of the balance of payment behavior in these nations. The empirical results show that India's GDP, as well as the inflation difference between Japan and India, are found to be very critical. The coefficient of India's GDP and inflation difference was positive while India's exchange rate and India's FDI were found to be negative. As the impact of India's exchange rate and India's FDI was negative, it is proof that an increase in India's exchange rate and India's FDI results in a decrease in the balance of payment, thereby the trade is ultimately affected. These results contain useful information that can be used by policymakers.